Food poisoning outbreak in Islamic Boarding School, Bantul, Yogyakarta, 2019 - Hafizha Muliani (BKM Public Health and Community Medicine, 2021)
Objective: On May 18, 2019, Kasihan I Primary Health Center reported to the Bantul District Health Office that there was a suspected food poisoning among students at Islamic Boarding School, Bantul. Investigation aims to confirm the outbreak, identify the source, and provide recommendations as preventive measures. Method: We conducted a retrospective cohort study. Case definition used during active case finding was a person of the Islamic Boarding School who experienced one of the symptoms of nausea, vomiting, diarrhea, abdominal pain with or without other symptoms in the period May 17-19, 2019. Data was collected through interviews using standardized questionnaires. Environmental investigations were carried out by interviewing food handlers and observing the kitchen environment. Food and fecal samples were sent to Yogyakarta Laboratory for testing. Data analysis using Chi Square test. Results: Of the 208 population at risk, there were 111 cases (AR = 53.4%). Main symptoms were nausea (76.6%), abdominal pain (60.4%), vomiting (39.6%), and diarrhea (39.6%). Epidemic curve was that of a common source with incubation periods of 1-47 hours 30 minutes (average 17.37 hours). Food suspected as the cause of this outbreak was sahur menu, chicken fried with sauce (RR = 2.50; p-value = 0.0023; 95% CI = 1.148-5.473). Potential risk factors was food had been cooked in large quantities and stored at room temperature for long periods of time. Laboratory results found Klebsiella pneumoniae bacteria in food and fecal samples. Conclusion: A food poisoning outbreak in Islamic Boarding School after consumption chicken fried with sauce. Improper food processing and storage were a potential risk factor for food contamination. We recommended the Bantul District Health Office to educate and monitor food handlers on food safety at Islamic boarding schools in Bantul.